2021
DOI: 10.3390/neurolint14010004
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Implant for Opioid Use Disorder

Abstract: The continued rise in the availability of illicit opioids and opioid-related deaths in the United States has left physicians, researchers, and lawmakers desperate for solutions to this ongoing epidemic. The research into therapeutic options for the treatment of opioid use disorder (OUD) began with the introduction of methadone in the 1960s. The approval of oral naltrexone initially showed much promise, as the drug was observed to be highly potent in antagonizing the effects of opioids while producing no opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…The fact that the abdominal region is the most preferred region in the literature has also been another factor affecting the change of the implantation site. [19][20][21][22][23][24] The data obtained were evaluated statistically to compare the implants placed in the back and the abdominal region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the abdominal region is the most preferred region in the literature has also been another factor affecting the change of the implantation site. [19][20][21][22][23][24] The data obtained were evaluated statistically to compare the implants placed in the back and the abdominal region.…”
Section: Methodsmentioning
confidence: 99%
“…18 In the studies in the literature, although it is reported that the abdominal region is the preferred implantation site in cases of opioid addiction due to its easy accessibility, there is no study on an ideal implantation site. [19][20][21][22][23][24] In our study, we aimed to evaluate and compare whether the back or abdominal region is most ideal for implantation by evaluating treatment compliance, surgical wound site, and complications in these patient groups.…”
mentioning
confidence: 99%
“…The rising number of opioid‐related fatalities in the United States is a growing national crisis, with reported deaths escalating from 9496 in 2001 to 80 411 in 2021 1,2 . This upsurge is attributed to the prevalence of illicitly produced fentanyl, which exhibits an estimated 50–100 times greater potency than morphine and has displayed resistance to usual doses of naloxone, a commonly employed medication for opioid overdose management 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…Naltrexone is presently used in the clinic for treating alcohol use disorder and manage opioid abuse. 11,12 The compound is considered a nonselective opioid receptor antagonist, although there is a significantly higher affinity for μ-receptors than for κ-and δ-receptors (Ki: 0.89 nM, 20.2 nM and 64.1 nM, respectively). 13 As a result, naltrexone has been found to produce a nearly complete blockade of μ-receptors in humans at a dose of 50 mg/ day, compared with 20% to 35% blockage of δ-receptors.…”
mentioning
confidence: 99%
“…The results of the current study therefore confirm the possibility of using certain opioids as ASMs, at least in specific conditions. Naltrexone is presently used in the clinic for treating alcohol use disorder and manage opioid abuse 11,12 . The compound is considered a nonselective opioid receptor antagonist, although there is a significantly higher affinity for μ‐receptors than for κ‐ and δ‐receptors (Ki: 0.89 nM, 20.2 nM and 64.1 nM, respectively) 13 .…”
mentioning
confidence: 99%